Analysis of Financial Performance Assessment Based on Du Pont System with Time Series Approach (TSA) and Cross Sectional Approach (CSA) Method (Case Studies on Textile Companies Listed on the Indonesia Stock Exchange for the 2017 - 2019 Period) - Farida Khairani Lubis; Lusi Elviani Rangkuti; Jalilah Ilmiha (Budapest International Research and Critics University, 2021)
The purpose of this study is to determine the financial performance assessment of textile companies listed on the Indonesia Stock Exchange 2017-2019 using the Du Pont System Time Series Approach and Cross Sectional Approach analysis methods, to determine the financial performance assessment of textile companies listed on the Indonesia Stock Exchange. 2017-2019 based on the Du Pont System Analysis method. The results of this study are performance appraisal based on the Du Pont system analysis which consists of PT. Polycem Indonesia, Tbk has an average value above the average value of the industry with that the company is said to be good, PT. Argo Pantes, Tbk has an average value above the industry average, with this the company's performance is said to be good, PT. Trisula Textile Industries, Tbk has an average value greater than the industry average, with this it is said that the company's performance is said to be good, PT. Eratex Djaja has an average value greater than the industry average which means that the company's performance is said to be good, PT. . Evershine has an average value above the industry average which means that the company's performance is said to be good.